Nuclear monomeric integrin αv in cancer cells is a coactivator regulated by thyroid hormone. Issue 8 (2nd May 2013) - Lin, Hung‐Yun; Su, Yee‐Fun; Hsieh, Meng‐Ti; Lin, Sharon; Meng, Ran; London, David; Lin, Cassie; Tang, Heng‐Yuan; Hwang, Jaulang; Davis, Faith B.; Mousa, Shaker A.; Davis, Paul J.
Abstract : Thyroid hormone induces tumor cell and blood vessel cell proliferation via a cell surface receptor on heterodimeric integrin αvβ3. We investigated the role of thyroid hormone‐induced internalization of nuclear integrin αv monomer. Physiological concentration of thyroxine (free T4, 10 –10 M), but not 3, 5, 3'‐triiodo‐L‐thyronine (T3 ), induced cellular internalization and nuclear translocation of integrin αv monomer in human non‐small‐cell lung cancer (H522) and ovarian carcinoma (OVCAR‐3) cells. T4 did not complex with integrin αv monomer during its internalization. The αv monomer was phosphorylated by activated ERK1/2 when it heterodimerized with integrin β3 in vitro. Nuclear αv complexed with transcriptional coactivator proteins, p300 and STAT1, and with corepressor proteins, NCoR and SMRT. Nuclear αv monomer in T4 ‐exposed cells, but not integrin β3, bound to promoters of specific genes that have important roles in cancer cells, including estrogen receptor‐α, cyclooxygenase‐2, hypoxia‐inducible factor‐1α, and thyroid hormone receptor β1 in chromatin immunoprecipitation assay. In summary, monomeric αv is a novel coactivator regulated from the cell surface by thyroid hormone for the expression of genes involved in tumorigenesis and angiogenesis. This study also offers a mechanism for modulation of gene expression by thyroid hormone that is adjunctive to the nuclear hormone receptor (TR)‐T3 pathway.—Lin, H.‐Y., Su, Y.‐F., Hsieh, M.‐T., Lin, S., Meng, M., London, D., Lin, C., Tang, H.‐Y., Hwang, J., Davis, F. B., Mousa, S. A.and Davis, P. J., Nuclear monomeric integrin αv in cancer cells is a coactivator regulated by thyroid hormone. FASEB J. 27, 3209–3216 (2013). www.fasebj.org